Blood-Brain Barrier Genomics, Proteomics, and New Transporter Discovery - Shusta, Eric V. (The American Society for Experimental NeuroTherapeutics, Inc., 2005)
Summary: The blood-brain barrier (BBB) is an impermeable cellular interface that physically separates the blood from the interstices of the brain. The endothelial cells lining the brain blood vessels form the principle barrier, and their unique phenotype is a consequence of dynamic interactions with several perivascular cell types present in the brain parenchyma. In addition, BBB dysfunction has been observed in the large majority of neurological diseases, but the causes of aberrant vascular behavior are generally unknown. Because of its barrier phenotype, drug delivery to the brain has also proven to be a very difficult task. Global genomics and proteomics analyses are currently being used to examine BBB function in healthy and diseased brain to better characterize this dynamic interface. It is becoming increasingly evident that these approaches have the potential to clarify the unique attributes of a healthy BBB, to identify therapeutic targets in diseased brain, and to identify novel conduits for noninvasive delivery of drugs against these targets. This review will discuss the application of genomics and proteomics to blood-brain barrier research and will offer views on the prospects of such approaches.